Ventral striatal hyperconnectivity during rewarded interference control in adolescents with ADHD. (September 2016) - Ma, Ili; van Holstein, Mieke; Mies, Gabry W.; Mennes, Maarten; Buitelaar, Jan; Cools, Roshan; Cillessen, Antonius H.N.; Krebs, Ruth M.; Scheres, Anouk
Abstract: Objective: Attention-deficit/hyperactivity disorder (ADHD) is characterized by cognitive deficits (e.g., interference control) and altered reward processing. Cognitive control is influenced by incentive motivation and according to current theoretical models, ADHD is associated with abnormal interactions between incentive motivation and cognitive control. However, the neural mechanisms by which reward modulates cognitive control in individuals with ADHD are unknown. Method: We used event-related functional resonance imaging (fMRI) to study neural responses during a rewarded Stroop color-word task in adolescents (14–17 years) with ADHD ( n  = 25; 19 boys) and healthy controls ( n  = 33; 22 boys). Results: Adolescents with ADHD showed increased reward signaling within the superior frontal gyrus and ventral striatum (VS) relative to controls. Importantly, functional connectivity analyses revealed a hyperconnectivity between VS and motor control regions in the ADHD group, as a function of reward-cognitive control integration. Connectivity was associated with performance improvement in controls but not in the ADHD group, suggesting inefficient connectivity. Conclusion: Adolescents with ADHD show increased neural sensitivity to rewards and its interactions with interference control in VS and motor regions, respectively. The findings support theoretical models of altered reward-cognitive control integration in individuals with ADHD.